2015
DOI: 10.3390/math3020481
|View full text |Cite
|
Sign up to set email alerts
|

The Complement of Binary Klein Quadric as a Combinatorial Grassmannian

Abstract: Given a hyperbolic quadric of PG(5, 2), there are 28 points off this quadric and 56 lines skew to it. It is shown that the (28 6 , 56 3 )-configuration formed by these points and lines is isomorphic to the combinatorial Grassmannian of type G 2 (8). It is also pointed out that a set of seven points of G 2 (8) whose labels share a mark corresponds to a Conwell heptad of PG(5, 2). Gradual removal of Conwell heptads from the (28 6 , 56 3 )-configuration yields a nested sequence of binomial configurations identica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In the second case, the permutation group is P = A 8 and the geometry is the configuration [28 6 , 56 3 ] on 28 points and 56 lines of size 3. In [18], it was shown that the geometry in question corresponds to the combinatorial Grassmannian of type Gr(2, 8), alias the configuration obtained from the points off the hyperbolic quadric Q + (5, 2) in the complex projective space P G(5, 2). Interestingly, Gr(2, 8) can be nested by gradual removal of a so-called 'Conwell heptad' and be identified to the tail of the sequence of 1 A different enlightning of the projective space P G(3, 2) appears in [17] with the connection to the Kirkman schoolgirl problem.…”
Section: Finite Geometry Of Small Exotic R 4 'S and Quantum Computingmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second case, the permutation group is P = A 8 and the geometry is the configuration [28 6 , 56 3 ] on 28 points and 56 lines of size 3. In [18], it was shown that the geometry in question corresponds to the combinatorial Grassmannian of type Gr(2, 8), alias the configuration obtained from the points off the hyperbolic quadric Q + (5, 2) in the complex projective space P G(5, 2). Interestingly, Gr(2, 8) can be nested by gradual removal of a so-called 'Conwell heptad' and be identified to the tail of the sequence of 1 A different enlightning of the projective space P G(3, 2) appears in [17] with the connection to the Kirkman schoolgirl problem.…”
Section: Finite Geometry Of Small Exotic R 4 'S and Quantum Computingmentioning
confidence: 99%
“…Recall that ∂W is the boundary of Akbulut cork W . The 28-letter permutation group P has two generators as follows P = 28|g 1 , g 2 with g 1 = (2, 4, 8, 6, 3)(5, 10, 15, 13, 9) (11,12,18,25,17) (14,20,19,24,21) (16,22,26,28,23), g 2 = (1, 2, 5, 11, 6, 7, 3)(4, 8, 12, 19, 22, 14, 9) (10,16,24,27,21,26,17) (13,20,18,25,28,23,15).…”
Section: Finite Geometry Of Small Exotic R 4 'S and Quantum Computingmentioning
confidence: 99%
See 1 more Smart Citation
“…In V (G 2 (7)), there exists a distinguished symplectic polar space W(5, 2) whose lines comprise three orbits of lines of type (α, α, α), (α, β, β), and (α, β, γ)-that is, the orbits whose cores feature an odd number of points of G 2 (7). Other prominent geometrical objects of V (G 2 (7)) are: a hyperbolic quadric Q + 0 (5, 2) ∈ W(5, 2) formed by 35 points of type α and 105 lines of type (α, α, α); a combinatorial Grassmannian G 2 (7) formed by 21 points of type β and 35 lines of type (β, β, β); and a Conwell heptad with respect to the above-defined Q + 0 (5, 2) represented by seven points of type γ (see also [17]). Figure 2.…”
Section: Veldkamp Space Of G 2 (7)mentioning
confidence: 99%
“…Another prominent geometrical objects of V(G 2 (7)) are: a hyperbolic quadric Q + 0 (5, 2) ∈ W(5, 2) formed by 35 points of type α and Table 2: The seven different types of lines of V(G 2 (7)). Type Form Core composition Number abcd:ef g (α, α, α) abef :cdg three mutually non-collinear points (ab,cd, and ef ) 105 cdef :abg abcd:ef g (α, α, β) abce:df g a line (abc) and a point (f g) 210 abcf g:de abc:def g (α, α, γ) def :abcg two disjoint lines (abc and def ) 70 abcdef :g abcd:ef g (α, β, β) ab:cdef g a line (ef g) and two non-collinear points (ab and cd) 105 cd:abef g abcd:ef g (α, β, γ) abcde:f g a Pasch configuration (abcd) and a point (f g) 105 abcdf g:e abcde:f g (β, β, β) abcdf :eg a Pasch configuration (abcd) 35 abcdg:ef abcde:f g (β, γ, γ) abcdef :g a Desargues configuration (abcde) 21 abcdeg:f 105 lines of type (α, α, α); a combinatorial Grassmannian G 2 (7) formed 21 points of type β and 35 lines of type (β, β, β); and a Conwell heptad with respect to the above-defined Q + 0 (5, 2) represented by seven points of type γ (see also [14]).…”
Section: Relevant Finite-geometrical Backgroundmentioning
confidence: 99%